2017
DOI: 10.1016/j.healun.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Eighth annual INTERMACS report: Special focus on framing the impact of adverse events

Abstract: Greater application of durable devices to patients with ambulatory heart failure will mandate more effective neutralization or prevention of major adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
941
7
14

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,105 publications
(1,014 citation statements)
references
References 4 publications
22
941
7
14
Order By: Relevance
“…Nearly half the cohort underwent post‐cardiotomy implantation, which generally has higher mortality, and in our cohort had 77% higher mortality risk than primary implantation, although this did not reach statistical significance in multivariable analysis. We found that males had much lower mortality risk than females after VAD implantation, a pattern previously reported in non‐CKD LVAD cohorts 27. The hemodynamic instability and clinical status at time of implantation, as reflected by the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) profile, is an important determinant of mortality,27 and is unknown in our cohort.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Nearly half the cohort underwent post‐cardiotomy implantation, which generally has higher mortality, and in our cohort had 77% higher mortality risk than primary implantation, although this did not reach statistical significance in multivariable analysis. We found that males had much lower mortality risk than females after VAD implantation, a pattern previously reported in non‐CKD LVAD cohorts 27. The hemodynamic instability and clinical status at time of implantation, as reflected by the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) profile, is an important determinant of mortality,27 and is unknown in our cohort.…”
Section: Discussionsupporting
confidence: 64%
“…We found that males had much lower mortality risk than females after VAD implantation, a pattern previously reported in non‐CKD LVAD cohorts 27. The hemodynamic instability and clinical status at time of implantation, as reflected by the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) profile, is an important determinant of mortality,27 and is unknown in our cohort. It is likely, however, that the severe chronic kidney disease and associated comorbidities are major contributors to the high mortality.…”
Section: Discussionsupporting
confidence: 64%
“…MCS devices, originally used for patients with AdHF as a bridge-to-transplant or bridge-to-recovery, now increasingly used as destination (lifelong) therapy, have the potential to outnumber HTx by a factor of 1:10 [26]. Because of this success, destination MCS is increasingly being offered to patients with challenging clinical profiles.…”
Section: Outcomes In Adhf Patients Undergoing Mcs/htx Adhf Patients Umentioning
confidence: 99%
“…За этот период времени клиниче-ская практика применения имплантируемых систем с непульсирующим потоком насчитывала более 20 000 случаев в 180 различных клиниках мира [6].…”
Section: Introductionunclassified